ANTI-MÜLLERIAN HORMONE AND HOMA-IR LEVELS IN PCOS PHENOTYPES - Al-Sanjary, Asmaa Abdulrazaq (Eastern Ukrainian Medical Journal, 2026)
Introduction: Polycystic ovary syndrome (PCOS) is a common endocrinopathy affecting women, with variable prevalence (8–13%) and clinical manifestations, and it comprises four main clinical phenotypes. Elevated anti-Müllerian hormone (AMH) levels and insulin resistance are associated with ovarian dysfunction and metabolic disturbances in PCOS. The present study sought to describe the distribution of patients among PCOS phenotypes, evaluate AMH and HOMA-IR levels, and determine any correlation between them. Methods: This was a prospective cross-sectional study of infertile women attending the outpatient infertility clinic in Mosul city. The ages of the included patients, who were enrolled between July 2023 and 2024, ranged from 18 to 39 years. PCOS was diagnosed according to the Rotterdam criteria, and patients were grouped into four phenotypes. On cycle days 2–5 (of a spontaneous or induced menstrual cycle), transvaginal ultrasound was performed to evaluate polycystic ovaries and follicle number; the ultrasound was repeated on cycle day 14 to assess the presence or absence of ovulation. Additionally, on cycle days 2–5, an early-morning blood sample was collected after 8 hours of fasting. Results: The 132 infertile women with PCOS enrolled in the study demonstrated distinct phenotype prevalence: types A and D were more prevalent (57.57% and 30.31%, respectively) than types B and C. The duration of infertility was an important factor in differentiating between types, with the shortest duration (2.5 years) observed in type B patients compared to other types (4.37–4.45 years). AMH levels showed clear differences across groups, with Types A and C having the highest levels and Type B the lowest. LH levels were highest in Types C and D and lowest in Type B. FSH levels were higher in Type A compared to Types B, C, and D. The LH:FSH ratio was highest in Types C and D, while Type B had the lowest ratio. The highest insulin resistance (HOMA-IR and fasting insulin levels) was observed in Type A patients. Type A also demonstrated a high miscarriage rate (26.3%), whereas Type B showed no history of miscarriage. Types C and D revealed a high rate of ovarian cysts (37.5%). A positive correlation was found between insulin resistance and BMI, as well as between AMH levels and ovarian follicle count. Conclusion: The majority of patients fell into Types A and D, with high AMH and HOMA-IR values. A positive correlation existed between AMH and ovarian follicle number, as well as between HOMA-IR and BMI; therefore, both should be evaluated in all PCOS phenotypes. The study underscores the interconnected nature of metabolic and reproductive dysfunction in PCOS.